Teasing and policing in a multilingual family — Negotiating and subverting norms and social hierarchies - Johnsen, Ragni Vik (Journal of Pragmatics, 2020)
This paper demonstrates how multilingual adolescents initiate language-directed teasing in family interaction and thus contribute to reinforcing or challenging social hierarchies and norms in the family. It investigates the case of a multilingual family living in Northern Norway (two parents and five children ranging from 3 to 18 years old). To a varying extent, and with varying degrees of competence, all family members use three languages in their daily lives: English, Spanish, and Norwegian. The data consists of self-recorded material of family interactions (9 h; 549 min) that were collected over the course of one year. A close interactional analysis shows how the siblings target linguistic production in teasing attacks, and use language-directed teasing as an interactional resource to position themselves and their family members. Drawing on Billig's (2005) theory of disciplinary humor, the article argues that playful corrections of perceived norm transgressions may be understood as situated (re)production and negotiation of social and linguistic norms, through which the young family members participate in the construction of the family as a community of practice.